INISIATIF-INISIATIF PROGRAM YANG DIKEMBANGKAN DALAM UPAYA IMPLEMENTASI REDD+ DI KALIMANTAN TIMUR - Tien Wahyuni (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2019)
As a commitment to support the Nationally Determined Contribution (NDC), the provincial government of East Kalimantan through the Green Growth Compact (GGC) Declaration in 2016 has agreed to build program initiatives or prototype initiatives. This paper aims to provide information on eight program initiatives developed and the involvement process of the parties which became the umbrella of the agreement in the operationalization activities. The collection of data and information was done through desk or document study, interview and observation. Data were analyzed with content analysis techniques. The eight initiatives of the program are: (1) strengthening the acceleration of implementation and achievement of Social Forestry; (2) institutional strengthening of Forest Management Units (KPH); (3) management of the essential ecosystem for orangutan corridor in the Wehea-Kelay Landscape area; (4) partnership development in the Mahakam Delta Area; (5) Berau Forest Carbon Program; (6) sustainable plantation development; (7) climate village and (8) garden and land fire control . The developed program initiatives aim to achieve the Green Kaltim goal by testing the impact of these activities and finding innovative solutions in addressing the challenges of developing and managing natural resources and require cross-sectoral cooperation.